Honour and shame as key concepts in Chrysostom"s exegesis of the Gospel of John - Stander, Hennie (HTS teologiese studies, 2003)
Recently, studies have illustrated that honour and shame were core values in the Mediterranean world in general and in the Bible too. These studies usually resort to classical sources to support the claims being made. Modern scholars, who take the historical-critical approach seriously, have come to realize the importance of reading the Bible according to its appropriate cultural context, which of necessity includes an appreciation of honour and shame as social core values. However, the article shows that patristic sources have been neglected by many scholars who study the social values of the ancient world. This article illustrates the importance of these values for patristic authors. John Chrysostom’s homilies on the Gospel of John are used as an example to prove how he employed values such as honour and shame as exegetical keys to unlock the meaning of John’s gospel.